WILL SALAS’ STRUGGLE AS A PROLETARIAN IN PURSUING EQUALITY REFLECTED IN “IN TIME” THE MOVIE - MUNIAGARA, ARIEF (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: [Social Class, In Time, Class Conflict, Mise-en-Scene]The social structure created by state capitalism principle oppresses the proletarian class, and because of the oppression, the conflicts of interest between classes are born. In a way to survive in life and pursuit for happiness, some philosophers think that the struggle of the oppressed class must be done. Struggle is the only solution for the proletarian class to bring happiness to their life. The researcher is interested in analyzing the conflict of interest between two social classes reflected in the movie entitled In Time. The researcher is also interested in analyzing the struggle of proletarian against bourgeoist capitalism system.This research uses the Marxism theory of social class and class conflict proposed by Karl Marx. Other than that, to support the analysis, the researcher uses Mise-en-scene to help the researcher analyze some scenes in the movie entitled In Time. This research is in form of textual analysis because the aim of this research is related to the content of the movie. In conducting the research, the researcher follows several steps to get the data.After analyzing the movie, the researcher found the triggers that lead to the struggle of proletarian class against the bourgeoist capitalism system. The struggle of proletarian against bourgeoist is represented by the main character, Will Salas. Will Salas’ struggle is triggered by the unfair system to the people in Ghetto. The purpose of Will Salas’ struggle is to bring back what belongs to people in Ghetto. So, people in Ghetto will get what they deserve and a better life.